Sayang Kalau Dilewatkan: Promo Tanggal Kembar dan Perilaku Berbelanja Impulsif di Kalangan Mahasiswa: Too Good to Miss: Double-Date Promotions and Impulsive Buying Behavior Among College Students - Putriani Nimpa (Universitas Muslim Maros, 2026)
Shopee's twin-date promotions (such as 9.9, 10.10, 11.11, and 12.12) have become a popular digital phenomenon among college students, particularly due to the significantly lower prices offered compared to regular days. While most studies on twin-date promotions still focus on the relationship between twin-date promotions and purchasing decisions, impulsive buying, and consumer behavior through a quantitative approach, this study aims to understand the factors that drive student interest in twin-date promotions and how these promotions influence their consumer behaviour. This study used a qualitative approach and was conducted in Makassar. We used in-depth interview and observation as two combined data collection methods. Ten college students participated in this study, whose age ranging between 19 and 23 years old, all of whom had experience shopping during Shopee's twin-date promotions. Twin-date promotions have become part of digital consumption culture. College students' interest to shop during twin-date promotions is influenced by various factors, such as significant discounts, free shipping, cashback and vouchers, and Fear of Missing Out (FoMO). Psychological factors such as the satisfaction of obtaining goods at lower prices, the desire not to miss out on promotions, and the urge to reward themselves are intertwining factors that motivate students to shop during twin-date promotions. However, shopping during twin-date promotions not only provides positive impacts, such as practical shopping experiences and lower prices, but also generates negative impacts, including excessive spending and consumptive behavior that may disrupt students' financial stability. The intensity of promotional offers encourages students to make impulsive purchases without careful planning, driven largely by momentary emotional impulses. As a result, students often experience uncontrolled spending and feelings of regret after making purchases.